Preterm birth recurrence after spontaneous preterm birth between 16-28 weeks: A national cohort study - Annabelle L. Van Gils; Anita C. Ravelli; Esmé I. Kamphuis; Brenda M. Kazemier; Eva Pajkrt; Martijn A. Oudijk; Marjon A. De Boer (European Journal of Obstetrics & Gynecology and Reproductive Biology: X)
Objective: To assess the risk of recurrent preterm birth following spontaneous extreme preterm birth between 16+0 - 27+6 weeks. Methods: A nationwide retrospective cohort study was conducted with data from the Perinatal Registry of the Netherlands. We included nulliparous women with a singleton pregnancy that ended in spontaneous preterm birth between 16+0 and 27+6 weeks of gestation without congenital anomalies or antenatal death between 2010–2014 and had a subsequent pregnancy in the 5 years following (2010–2019). The primary outcome of this study was recurrent preterm birth < 37 weeks. Results: In total, 1011 women with linked pregnancies were included. The risk of preterm birth < 37 weeks with prior spontaneous birth between 16+0-19+6, 20+0-23+6, and 24+0-27+6 weeks was respectively 19.0 %, 29.5 % and 27.6 %. The risk of subsequent preterm birth < 24 weeks was 5.8 %, 7.2 % and 4.3 %. A short interpregnancy interval of 0–3 months was associated with increased odds for recurrent preterm birth < 32 weeks (OR 2.3 95 % CI 1.4–3.7) and preterm birth < 37 weeks (OR 1.8 95 % CI 1.2–2.6). Conclusion: Patients with previous spontaneous preterm birth from 16 weeks GA onwards are at high risk for recurrent preterm birth and should be regarded as such in the consideration of preventive measures to prevent recurrent adverse pregnancy outcomes.